MAKNA TRANSENDENTAL PADA FOTO ALAM - Hendy Yuliansyah (Jurusan Seni Rupa ISBI Bandung, 2015)
Photography is one of the artworks dominated by intensity of light. It falls into category of artworks that affect human civilization. With creativity and sensitivity tonatural phenomena, techniques of pure photography and journalism produce stunning natural photography. Nature photography visualizes the relationships between nature and human, as well as and God the Almighty. The research found out that the visualization of nature expressed through the media of photos contains deep transcendental meanings. Visualizationof color, composition, and image object generates intense transcendental meanings.Keywords: Design, Photography, Composition, Transcendental, Colour___________________________________________________________________ Fotografi merupakan salah satu karya seni yang didominasi oleh intensitas cahaya.Tergolong ke dalam kategori karya seni yang mempengaruhi peradaban manusia.Dengan kreativitas dan kepekaan terhadap fenomena alam, maka teknik fotografi murni, dan jurnalistik, menghasilkan fotografi alam yang menakjubkan.Fotografi alam, memvisualkan hubungan alam dan manusia, sekaligus kepada Tuhan Yang Maha kuasa.Dari penelitian ini, visualisasi alam yang diungkap melalui media foto mengandung makna transendental yang dalam.Visualisasi warna, komposisi, termasuk objek foto menghasilkan makna transendental yang kuat.Kata Kunci: Desain, Fotografi, Komposisi, Transendental, Warna